2019
DOI: 10.1039/c8fd00238j
|View full text |Cite
|
Sign up to set email alerts
|

On the benefits of using multivariate analysis in mass spectrometric studies of combustion-generated aerosols

Abstract: Building on a recently proposed comprehensive methodology, we propose herein a comparative analysis of soot particles produced by three different sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 64 publications
(11 reference statements)
2
22
0
Order By: Relevance
“…PAHs comprising more than four rings were classified as non-volatile as they were observed in the PM in their study. Note that slightly different classes have also been defined elsewhere in the literature Elghawi et al, 2010;Sun et al, 2006). In our study, we largely found compounds consisting of one and two aromatic rings on back filters, while PAHs of m/z 176-242 were found on both back and front filters and those of m/z ≥ 252 predominantly on front filters.…”
Section: Multivariate Data Analysis: Principal Component Analysis (Pca)supporting
confidence: 59%
See 1 more Smart Citation
“…PAHs comprising more than four rings were classified as non-volatile as they were observed in the PM in their study. Note that slightly different classes have also been defined elsewhere in the literature Elghawi et al, 2010;Sun et al, 2006). In our study, we largely found compounds consisting of one and two aromatic rings on back filters, while PAHs of m/z 176-242 were found on both back and front filters and those of m/z ≥ 252 predominantly on front filters.…”
Section: Multivariate Data Analysis: Principal Component Analysis (Pca)supporting
confidence: 59%
“…The sorbents are placed in series, i.e., one after the other in the exhaust line. The soluble organic fraction is then extracted off-line from the sorbent (filter and/or resin) for subsequent gas chromatography-mass spectrometry (GC-MS) analyses Elghawi et al, 2010;Sun et al, 2006). However, such solvent extraction methods exhibit recovery rates that are highly dependent upon the technique applied and the nature of PAHs a priori present.…”
Section: Introductionmentioning
confidence: 99%
“…CC BY 4.0 License. and 2 SIMS polarities) following the procedure detailed in Popovicheva et al (2017), Irimiea et al (2018), and Duca et al (2019). Further information can also be found in Sect.…”
Section: Multivariate Data Analysis: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…7. Cnfragments are commonly considered as markers of the EC content (Duca et al, 2019;Pagels et al, 2013;Popovicheva et al, 2017). For instance, Pagels et al (2013) used the sum of Cn -(n = 2-4) fragment signals as a marker of EC in aerosol time-of-flight mass spectrometer (ATOFMS) measurements for wood stove PM emissions and the same marker ions have been used to discriminate diesel from biodiesel PM emissions by Popovicheva et al (2017).…”
mentioning
confidence: 99%
“…We recently showcased the advantages of using advanced statistical techniques (Duca et al, 2019;Irimiea et al, 2018Irimiea et al, , 2019 to highlight subtle differences in the chemical composition of various samples. It is also very useful to confirm initial trends deduced from a descriptive approach of the mass spectra with a more quantitative approach such as that provided by the statistical analyses.…”
Section: ) Poormentioning
confidence: 99%